2011
DOI: 10.1186/1477-7525-9-41
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life associated to chronic pelvic pain is independent of endometriosis diagnosis-a cross-sectional survey

Abstract: BackgroundPain is strongly related to poor quality of life. We performed a cross-sectional study in a universitary hospital to investigate quality of life in women suffering from chronic pelvic pain (CPP) due to endometriosis and others conditions.MethodsFifty-seven patients aged between 25 and 48 years-old submitted to laparoscopy because of CPP were evaluated for quality of life and depressive symptoms. Quality of life was accessed by a quality of life instrument [World Health Organization Quality of Life As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 27 publications
3
72
1
15
Order By: Relevance
“…Another investigation found equivalent rates of depression and anxiety in subjects with CPP and migraine 21 , and two others found no differences when comparing CPP groups with different etiologies 27,37 .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Another investigation found equivalent rates of depression and anxiety in subjects with CPP and migraine 21 , and two others found no differences when comparing CPP groups with different etiologies 27,37 .…”
Section: Resultsmentioning
confidence: 95%
“…From these, five studies [24][25][26][27][28] used an observational descriptive design and the remaining 13 8,20,21,[29][30][31][32][33][34][35][36][37][38] used a case-control design. Most of the studies were conducted in the United States (n = 6) and Brazil (n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [13] vulvodynia patients reported lower quality of life than kidney transplant recipients or people with prior osteoporosis-related fracture. In another study, chronic pelvic pain was associated with worse quality of life, independent of the causal factor [23]. Considering these results, we suggest that reducing vulvodynia related pain is the best approach to improve patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%